DEVELOPING STUDENTS’ HANDOUT OF READING TEXT FOR EIGHTH GRADE STUDENTS - Isnawati Isnawati; Elanneri Kareni; Natalina Asi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The goal of this research is to create a student handout for eighth graders. The research was carried out in an R&D manner. Students' requirements were first assessed through observational guidance, and then more data was gathered using questionnaires and documents. Students from SMP in the eighth grade participated in this study. The researcher used some of the ADDIE model's recommendations when creating the new material. Analysis, design, development, implementation and evaluation are all terms used to describe these steps in the process. A thematic analysis of the qualitative data was performed. According to the findings of the analysis stage, students require additional material in the form of handouts that focuses on three different text kinds. As a consequence of observation and analysis, the researcher will design and build the materials. The researcher must validate the product before it can be made available to end customers. Finally, the study's findings demonstrate that the handout provided to eighth-grade students at SMP meets their educational needs.